If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(2b + 1) + -3b = 29 Reorder the terms: 7(1 + 2b) + -3b = 29 (1 * 7 + 2b * 7) + -3b = 29 (7 + 14b) + -3b = 29 Combine like terms: 14b + -3b = 11b 7 + 11b = 29 Solving 7 + 11b = 29 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 11b = 29 + -7 Combine like terms: 7 + -7 = 0 0 + 11b = 29 + -7 11b = 29 + -7 Combine like terms: 29 + -7 = 22 11b = 22 Divide each side by '11'. b = 2 Simplifying b = 2
| 4a(a^4)7a=a(4a^3)+20 | | 6x^2y+8xy+2= | | 4x/4=29/8 | | 20/10=N/2 | | Sinx=0.234 | | -2x-6+-0.25x-3+90=180 | | 2138.9994=3.14r^2 | | -32c/(5*9) | | X11/4 | | T/5=-5/7 | | 2318.9994=3.14r^2 | | 3x-17*5=-66 | | 4x+5y=10.45 | | 2.27*34= | | 0.16(y-6)+0.10y=0.04y-0.3 | | 4(5+3x)=-52 | | 7(a+2)=-2(a-2) | | 3x+1y=3.85 | | 12n=162 | | (5a-3b)+(2a+6b)= | | x(x-6)=x^2+5x+4 | | Y+23=111 | | 2(t-4)+6t=4(2t+3)-9 | | 4x-3+73=90 | | 4s-10=8-2s | | X-24=53 | | 4ln(5x+4)=22 | | g(3y)x-2x^2= | | 3(2c+1)=2(4c-1) | | 7n=219 | | 15d=3d | | (m-1)x^2-2mx-m-4=0 |